59.5k views
5 votes
Find the solution set by factoring and using the zero product rule or by using the quadratic formula

3x^2-x-1=0

enter your answer in fractional form using exact roots

User Cloudcop
by
5.7k points

2 Answers

0 votes

Answer:


x = (1)/(6) + ( √(13) )/(6) \: or
\: x = (1)/(6) - ( √(13) )/(6)

Explanation:

We are given the following quadratic equation and we are to find its roots:


3x^2-x-1=0

Since we cannot factorize it, we will use the quadratic formula
x = \frac{ - b \pm \sqrt{ {b}^(2) - 4ac } }{2a}

Substituting the given values in the above formula to get:


x = \frac{ - ( -1) \pm \sqrt{ { (- 1)}^(2) - 4(3)( - 1) } }{2(3)}


x = \frac{1\pm \sqrt{ { 1} +12 } }{6}


x = \frac{1\pm \sqrt{ {13 } } }{6}

So the roots are:


x = (1)/(6) + ( √(13) )/(6) \: or
\: x = (1)/(6) - ( √(13) )/(6)

User Travis Parks
by
5.4k points
2 votes
Answer:
The solution set is:
{
x = (1)/(6) + ( √(13) )/(6) \: or \: x = (1)/(6) - ( √(13) )/(6)}

Explanation:

Comparing the general equation,


a{x}^(2) + bx + c = 0

to


3{x}^(2) - x - 1 = 0

It can be testified that,


a = 3


b = - 1

and


c= - 1

The quadratic formula is given by:


x = \frac{ - b \pm \sqrt{ {b}^(2) - 4ac } }{2a}

We now substitute the values of a, b and c into the formula


x = \frac{ - ( -1) \pm \sqrt{ { (- 1)}^(2) - 4(3)( - 1) } }{2(3)}


\implies x = \frac{1\pm \sqrt{ { 1} +12 } }{6}


\implies x = \frac{1\pm \sqrt{ {13 } } }{6}


\implies x = (1)/(6) + ( √(13) )/(6) \: or \: x = (1)/(6) - ( √(13) )/(6)
User Shruggie
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.